6. Deep Inspiration Breath Hold of Left-sided Breast cancer radiotherapy: predictive parameters for patient selection. (December 2018) - Naccarato, S.; Fiorentino, A.; Mazzola, R.; Fersino, S.; Giaj Levra, N.; Ricchetti, F.; Sicignano, G.; Gregucci, F.; Figlia, V.; Alongi, F.; Ruggieri, R.
Abstract : Purpose: To investigate possible predictive anatomical features correlating to cardiac and left-lung dose sparing by deep inspiration breathhold (DIBH) technique compared to freebreathing (FB) for left-sided whole breast radiation therapy (RT). Materials and Methods: Twenty consecutive patients who underwent (DIBH) left-sided breast RT had both FB and DIBH CT simulation. All patients were planned with two 6 MV-flattening-filter-free FFF (DIHB) and two/four (FB) 6 MV IMRT tangential fields, with prescription of 50 Gy/25 fr to whole breast and 60 Gy to simultaneous integrated boost (SIB). Mean dose and dosevolume metrics (V5Gy, V10Gy, V20Gy) were analyzed and compared for heart and left-lung for both FB and DIBH techniques. Correlation analyses were performed between such dose metrics and patient (FB) anatomic features: maximal heart distance and length (MHD, MHL), maximal lung distance (MLD), chest wall rise (CWH) (Fig. 1). Paired t-test or Wilcoxon signed-rank test was applied to compare differences in the dose metrics between the two techniques and linear regression was used for data analysis with significance level of p ≤ 0.05. Results: All dose metrics for the heart and left-lung were significantly reduced (p < 0.01) with DIBH. MHL(FB) correlated with mean (Pearson's coefficient r = 0, 60, p = 0, 02), V10Gy (r = 0, 54, p = 0, 03) and V5Gy (r = 0, 66, p = 0, 006) of heart dose reduction by DIBH. A positive correlation was observed between CWH and decrease in mean dose (r = 0, 56, p = 0, 01), V20Gy (r = 0, 48, p = 0, 03), V10Gy (r = 0, 63, p = 0, 003) and V5Gy (r = 58, p = 0, 007) for lung by DIBH (Fig. 2). MHD(FB) and MLD(FB) showed a weak correlation with dosimetric changes. Conclusion: In this patient cohort, DIBH technique has been shown to reduce dose to the heart and left-lung. MHL(FB) and CWH served as significant predictors for heart and left-lung dose sparing by DIBH. These parameters can be easily measured at the time of CT simulation and thus may be used as simple and quick tool to determine which patient may benefit from a DIBH technique.